Subglacially precipitated carbonates record geochemical interactions and pollen preservation at the base of the Laurentide Ice Sheet on central Baffin Island, eastern Canadian Arctic - Refsnider, K.; Miller, Gifford; Fogel, M.; Frechette, B.; Bowden, R.; Andrews, J.; Farmer, G. (Academic Press, 2014)
Themineralogy and isotopic compositions of subglacially precipitated carbonate crusts (SPCCs) provide information on conditions and processes beneath former glaciers and ice sheets. Here we describe SPCCs formed on gneissic bedrock at the bed of the Laurentide Ice Sheet (LIS) during the last glacial maximum on central Baffin Island. Geochemical data indicate that the Ca in the crusts was likely derived from the subglacial chemical weathering Ca-bearing minerals in the local bedrock. C and Sr isotopic analyses reveal that the C in the calcite was derived predominantly fromolder plant debris. The d18O values of the SPCCs suggest that these crusts formed in isotopic equilibrium with basal ice LIS preserved in the Barnes Ice Cap (BIC). Columnar crystal fabric and the predominance of sparite over micrite in the SPCCs are indicative of carbonate precipitation under open-system conditions. However, the mean d18O value of the calcite crusts is ~10‰ higher than those of primary LIS ice preserved in the BIC, demonstrating that SPCCs record the isotopic composition of only basal ice. Palynomorph assemblages preserved within the calcite and basal BIC ice include species last endemic to the Arctic in the early Tertiary. The source of these palynomorphs remains enigmatic.